1965
DOI: 10.1172/jci105249
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Aldosterone in Several Experimental Situations with Altered Aldosterone Secretion*

Abstract: In an earlier study (1), the rate of metabolism of aldosterone was found to be decreased in dogs with chronic passive congestion of the liver secondary to thoracic inferior vena caval constriction. After hepatectomy of these animals and of normal dogs, the metabolism of aldosterone was almost abolished. It was suggested that the decreased aldosterone metabolism during liver congestion might be secondary to decreased hepatic blood flow and associated hepatic anoxia. More recently, Tait and his colleagues (2, 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1966
1966
1974
1974

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The following three possibilities occur to us: 1) The portacaval anastomosis, by decreasing hepatic blood flow, might keep the plasma volume from falling to normal. Evidence has been presented recently to show that hepatic degradation of aldosterone is dependent on liver blood flow (52)(53)(54), and it is possible that a reduction in hepatic blood flow produced by portacaval anastomosis of either the end-to-side or side-to-side variety (36) could elevate the plasma aldosterone concentration sufficiently to keep the plasma volume expanded.…”
Section: Plasma Volume In Functional Renal Failurementioning
confidence: 99%
“…The following three possibilities occur to us: 1) The portacaval anastomosis, by decreasing hepatic blood flow, might keep the plasma volume from falling to normal. Evidence has been presented recently to show that hepatic degradation of aldosterone is dependent on liver blood flow (52)(53)(54), and it is possible that a reduction in hepatic blood flow produced by portacaval anastomosis of either the end-to-side or side-to-side variety (36) could elevate the plasma aldosterone concentration sufficiently to keep the plasma volume expanded.…”
Section: Plasma Volume In Functional Renal Failurementioning
confidence: 99%
“…A parallel functional change which is secondary to decreased hepatic blood flow is the decreased plasma clearance of aldosterone (13).…”
Section: Figurementioning
confidence: 99%
“…Tait, Tait, Little, and Laumas (1) described the disappearance of aldosterone from plasma of normal man in terms of a two compartment system. Davis, Olichney, Brown, and Binnion (2) showed that the volumes of distribution and rates of clearance of aldosterone are reduced in dogs with experimental heart failure and low cardiac output. Our findings indicate that marked alterations in distribution and clearance of aldosterone are present in patients with congestive failure.…”
mentioning
confidence: 99%